The effectiveness of signaling principle in virtual reality courseware towards achievement of transfer learning among students with different spatial ability - Yahaya, Wan Ahmad Jaafar Wan; Ahmad, Awaatif (AIP conference proceedings, 2017)
Past research revealed that students and society, in general, are relatively under-skilled in performing the practice of Islamic funeral management which is one of the “ibadah fardu kifayah” (a legal obligation that must be discharged by the Muslim community as a whole) in Islam. Participation among youth in managing funerals is relatively low, partly due to the ineffectiveness of the instructional approach. This paper aims to examine the effectiveness of the signaling principle in virtual reality courseware pertaining to the topic of Islamic Funeral Management in the Islamic Education subject to ensure the accomplishment of transfer learning among students with different spatial abilities. The study comprises of two phases namely the courseware development phase and treatment phase. The courseware development employs the Instructional Design Model by Alessi and Trollip. Besides that, the courseware is integrated with components of CLE, principles in Theory of CATLM and signaling principle in multimedia learning. The sample consisted of 130 Form Two students who were selected randomly from four Malaysian secondary schools. They were divided into two experimental groups with 63 students in group one and 67 students in group two. The experimental group one used VR courseware without the signaling principle (VRTI) while experimental group two used the VR courseware with the signaling principle (VRDI). The experiment lasted for three weeks. ANOVA was utilised to analyse the data from this research. The findings showed significant differences between students who used VRDI in the transfer of learning compared to students who used VRTI.